PELATIHAN PEMBUATAN MODEL 3D ALAT PERAGA EDUKASI HIDROLOGI BERBASIS AUGMENTED REALITY UNTUK GURU - Budi Arifitama (Jurnal Pengabdian Masyarakat Multidisiplin, 2020)
Augmented reality in Indonesia has been widely used as a media aids in teaching in the classroom, to enhance a better learning interaction between teachers and students. Students can learn independently by observing augmented reality objects that are developed without the need to be guided. Unfortunately developing an augmented reality application takes a lot of effort especially for teachers, there are not many teachers who can develop an augmented reality application. Based on these problems, through the APSI organization, community service activities were carried out in the form of training on making 3D models based on augmented reality which was attended by representatives of 15 teachers from Jadebotabek. The training activities were divided into 3 sessions, namely the first session through the lecture method, the second session the guided tutorial method and the last session with training. The results of the implementation of this training are the teacher is able to make augmented reality applications independently and is able to make augmented reality based hydrological teaching aids that can be used to enrich learning in the classroom.